Study Protocol: Development of an economic trait prioritization for Tilapia in Nigeria - Cole, Steven (Abacusbio, 2023)
The aim(s) of this study are 1. to investigate the variability between production systems, across geographies, and related to gender within and between systems in Nigeria in a) economic model input parameters, and b) Tilapia trait preferences; 2. to incorporate this variability into trait economic weights for a breeding objective and a selection index or selection indexes that meets the needs of the Nigerian Tilapia industry.